HEAT TRANSFER IN AN ULTRASONIC PROCESSING CELL: PRELIMINARY MEASUREMENTS - Yusaf, Talal; Buttsworth, David R.; Deeth, Hilton C. (Emirates Journal of Food and Agriculture, 2017)
To take full advantage of the efficiencies offered by ultrasonic processing in various applications, it can be important to minimize or utilize the ultrasonic energy that is removed from the processing volume in the form of heat. In the present work, a small volume of water is exposed to approximately 400W of ultrasonic power at 20kHz. Measurements of the convective heat transfer at the surface of the processing cell were obtained through a transient heat transfer experiment. Details of the experimental arrangement as well as the preliminary experimental heat transfer results are discussed. It was found that the overall heat losses in the present arrangement represents less than 5% of the applied ultrasonic power.